2022
DOI: 10.2147/jbm.s367990
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Haematologic Profiling of Regular Blood Donors Revealed Health Benefits

Abstract: Background: Blood banks have been suffering a shortage of blood worldwide due to limited donations. By and large, it is widely believed that blood donation has multiple health benefits. However, there are limited studies that support it. As a result, assessing the biochemical profiles of the regular blood donors is indispensable to evaluating an individual's risk for chronic inflammation. Objective: We strived to compare lipid and haematological profiles of the regular and first-time blood donors in the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, this treatment often resulted poor outcome since patients were not adhere to the statin treatment, showed intolerance or resistance of statin [4]. Previous study revealed that hyperlipidemic status was corelated with frequency of blood donation [5], [6]. However, there was insufficient research and data about the cholesterol level and its influencing factors among blood donors in the world, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, this treatment often resulted poor outcome since patients were not adhere to the statin treatment, showed intolerance or resistance of statin [4]. Previous study revealed that hyperlipidemic status was corelated with frequency of blood donation [5], [6]. However, there was insufficient research and data about the cholesterol level and its influencing factors among blood donors in the world, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%